A comparison between different existing methods used to separate epidermal cells from skin biopsies for autologous transplantation - Mohsen Khosravi Maharlooei; Ali Akbar Mohammadi; Ali Farsi; Iman Ahrari; Armin Attar; Ahmad Monabati (Wolters Kluwer Medknow Publications, 2011)
Background: Burn surgeons use autologous skin graft technique for patients, but a challenge remains for large surface wounds. Recently, a method was described which used a small piece of skin to cover a 70 times greater surface by spraying epidermal cells on injured skin. We designed a comparative study to find the best method to make an epidermal cell suspension. Materials and Methods : Eleven discarded skin samples were sent to our laboratory from Ghotboddin Burn Hospital, Shiraz. Each sample was sliced into four small pieces (1 cm 2 ) and each piece was treated with a different chemical including sodium bromide (2N) and (4N), ammonium hydroxide (2N), and trypsin (0.05%) for 20 minutes. The epidermis and dermis were separated using forceps. Trypsin was added to all samples (except the trypsinized sample) to begin the intercellular detachment. Afterward, epidermis was sliced into small pieces followed by filtration and centrifugation. Cells were counted using hemocytometer. Identification of keratinocytes and melanocytes was made through immunocytochemical staining for cytokeratin and melanosome antigens, respectively. Results: There was a significant difference in alive cell counts comparing cells obtained from NaBr (4N) method to other methods. Considering total cell count and alive cell count, NaBr (4N) yielded the most cells. Immunocytochemical staining showed that in all methods, some cells are stained positively for cytokeratin antibody and some for melanosome antibody. Conclusion: Although recent papers had advised trypsin method to make a cell suspension to use for burn patients, we found that NaBr (4N) method yields more alive cells and less toxicity.